Analisis Hubungan Pemberian ASI Eksklusif dan Pendidikan Ibu terhadap Perkembangan Bayi - Dewi Sartika Siagian; Sara Herlina (Jurnal Kesmas Asclepius, 2019)
The purpose of this study was to determine the relationship of exclusive breastfeeding and mother's education on infant development. This research is a quantitative observational analytic with cross sectional design. The results of univariate analysis show that most babies get exclusive breastfeeding as many as 46 people (55.4%), low education as many as 56 people (67.5%) and most of the normal development of 47 people ( 56.6%). The results of bivariate analysis of exclusive breastfeeding for infant development by chi square test obtained P value <0,000. Conclusions, there is a relationship between exclusive breastfeeding on infant development and bivariate analysis of maternal education on infant development. There is a relationship between mother's education and infant development. Keywords: Exclusive ASI, Mother's Education, Infant Development